Regulation of ferroptosis by PI3K/Akt signaling pathway: a promising therapeutic axis in cancer - Su, Hua; Peng, Chao; Liu, Yang (Frontiers in Cell and Developmental Biology, 2024)
The global challenge posed by cancer, marked by rising incidence and mortality rates, underscores the urgency for innovative therapeutic approaches. The PI3K/Akt signaling pathway, frequently amplified in various cancers, plays a pivotal roleis central in regulating essential cellular processes. Its dysregulation, often stemming from genetic mutations, significantly contributes to cancer initiation, progression, and resistance to therapy. Concurrently, ferroptosis, a recently discovered form of regulated cell death, characterized by iron-dependent processes and lipid reactive oxygen species buildup, holds implications for diseases, including cancer.Exploring the interplay between the dysregulated PI3K/Akt pathway and ferroptosis unveils potential insights into the molecular mechanisms driving or inhibiting ferroptotic processes in cancer cells. Evidence suggests that inhibiting the PI3K/Akt pathway may sensitize cancer cells to ferroptosis induction, offering a promising strategy to overcome drug resistance. This review aims to provide a comprehensive exploration of this interplay, shedding light on the potential for disrupting the PI3K/Akt pathway to enhance ferroptosis as an alternative route for inducing cell death and improving cancer treatment outcomes.